Fracture strength and bending of all-ceramic and fiber-reinforced composites in inlay-retained fixed partial dentures - Serkan Saridag; Atilla Gokhan Ozyesil; Gurel Pekkan (Elsevier, 2012)
Background/purpose: In the most recent decade, the use of all-ceramic and fiber-reinforced composites as inlay-retained fixed partial dentures has increased. There are limited studies of comparisons of the mechanical strength and bending of these restorations. The aim of this in vitro study was to compare the fracture strength and the amount of bending in all-ceramic and fiber-reinforced composite inlay-retained fixed partial dentures. Materials and methods: Forty mandibular premolars and 40 mandibular molars were collected. The specimens were randomly divided into four groups of 10 molars and premolars within each group, each with box-shaped proximal preparations. Two different all-ceramic systems (IPS e.max Press and ICE Zirkon) and two different fiber-reinforced composite systems (EverStick and Vectris) with a connector size of 16 mm2 were used to restore prepared abutment teeth. After thermal cycling (5 and 55°C×5000), a vertical force was loaded to the center of the inlay-retained fixed partial dentures at a crosshead speed of 0.5 mm/min. Failure types of specimens were examined with a stereomicroscope and radiography. Statistical analysis was performed using one-way analysis of variance (ANOVA) and Mann-Whitney-U tests (α=0.05). Results: Fracture strengths were significantly higher in the ICE Zirkon (1540 N) and EverStick specimens (1057 N) than in the Vectris (794 N) and IPS e.max Press specimens (606 N) (P<0.001). The amount of bending was significantly greater in the EverStick (1.94 mm) and Vectris (1.87 mm) specimens than in the ICE Zirkon (1.07 mm) and IPS e.max Press specimens (1.18 mm) (P<0.001). Conclusions: Zirconia-based ceramic inlay-retained fixed partial dentures demonstrated the highest fracture strength. The fiber-reinforced composite inlay-retained fixed partial dentures demonstrated higher bending values than did the all-ceramic inlay-retained fixed partial dentures.